2018
DOI: 10.1016/j.ydbio.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

An optogenetic approach to control protein localization during embryogenesis of the sea urchin

Abstract: Light inducible protein-protein interactions have been used to manipulate protein localization and function in the cell with utmost spatial and temporal precision. In this technical report, we use a recently developed optogenetic approach to manipulate protein localization in the developing sea urchin embryo. A photosensitive LOV domain from Avena sativa phototropin1 cages a small peptide that binds the engineered PDZ domain (ePDZ) upon blue light irradiation. Using this system, mCherry tagged proteins fused w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To avoid unwanted optogenetic activation while imaging, a minimum amount of laser power (0.1~0.3% for 488 nm and 1~3% for 561 nm) was also used. These conditions were previously documented to induce Vasa-less micromeres in this embryo 44 . In these embryos with optogenetics cassettes, translation activity (detected by FIAsH; green) dispersed from the spindle to the cytoplasm upon blue light irradiation, resulting in no FIAsH enrichment in micromeres.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…To avoid unwanted optogenetic activation while imaging, a minimum amount of laser power (0.1~0.3% for 488 nm and 1~3% for 561 nm) was also used. These conditions were previously documented to induce Vasa-less micromeres in this embryo 44 . In these embryos with optogenetics cassettes, translation activity (detected by FIAsH; green) dispersed from the spindle to the cytoplasm upon blue light irradiation, resulting in no FIAsH enrichment in micromeres.…”
Section: Resultsmentioning
confidence: 53%
“…The photosensitive LOVpep (LOV) domain from Avena sativa phototropin1 undergoes a conformational change and binds to the engineered PDZb1 (ePDZ) domain upon blue light irradiation 41 43 . This binding is reversible and can be released when blue light irradiation is ceased or significantly decreased, providing good temporal control of protein-protein binding 44 . To recruit Vasa to an ectopic sub-cellular region, Vasa-mCherry was tagged to LOV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…al demonstrated that in ChR2-sensitised ventricular myocytes, action potentials can be easily regulated using certain light stimuli [31]. Similarly, optogenetics is also becoming increasingly applied in developmental studies, most notably as a method for controlling protein localization during embryogenesis [32]. These examples prove that the innovative method not only created space for major developments in neuroscience-related areas, but also many others.…”
Section: Global Revolution and Complicated Futurementioning
confidence: 99%
“…Optogenetics, or the genetic encoding of light-controlled proteins, allows for non-invasive investigation of biological processes with precise spatiotemporal control . Light-responsive proteins, such as phytochrome and cytochrome photoreceptors, have been used to investigate signaling pathways, , transcription, , and protein localization. While light-responsive protein domains can enable precise spatiotemporal control of the specified system, a protein fusion is always needed. Conversely, photocaged proteins, or proteins bearing a photolabile moiety that blocks a specified function before cleavage and activation with light, require only a point mutation for the introduction of an unnatural amino acid (UAA) while still maintaining precise optical control.…”
Section: Introductionmentioning
confidence: 99%